Time-dependent alteration in the chemoreflex post-acute lung injury - Kamra, Kajal; Karpuk, Nikolay; Adam, Ryan; Zucker, Irving H.; Schultz, Harold D.; Wang, Han-Jun (Frontiers in Physiology, 2022)
Acute lung injury (ALI) induces inflammation that disrupts the normal alveolar-capillary endothelial barrier which impairs gas exchange to induce hypoxemia that reflexively increases respiration. The neural mechanisms underlying the respiratory dysfunction during ALI are not fully understood. The purpose of this study was to investigate the role of the chemoreflex in mediating abnormal ventilation during acute (early) and recovery (late) stages of ALI. We hypothesized that the increase in respiratory rate (fR) during post-ALI is mediated by a sensitized chemoreflex. ALI was induced in male Sprague-Dawley rats using a single intra-tracheal injection of bleomycin (Bleo: low-dose=1.25 mg/Kg or high-dose=2.5 mg/Kg) (day 0) and respiratory variables- fR , Vt (Tidal Volume), and V̇E (Minute Ventilation) in response to 10% hypoxia (10% O2, 0% CO2) and 5% hypercapnia/21% normoxia (21% O2, 5% CO2) were measured weekly from W0-W4 using whole-body plethysmography (WBP). Our data indicate sensitization (∆fR= 93±31 bpm, p<0.0001) of the chemoreflex at W1 post-ALI in response to hypoxic/hypercapnic gas challenge in the low-dose bleo (moderate ALI) group and a blunted chemoreflex (∆fR= -0.97±42 bpm, p<0.0001) at W1 post-ALI in the high-dose bleo (severe ALI) group. During recovery from ALI, at W3-W4, both low-dose and high-dose groups exhibited a sensitized chemoreflex in response to hypoxia and normoxic-hypercapnia. We then hypothesized that the blunted chemoreflex at W1 post-ALI in the high-dose bleo group could be due to near maximal tonic activation of chemoreceptors, called the ‘ceiling effect’. To test this possibility, 90% hyperoxia (90% O2, 0% CO2) was given to bleo treated rats to inhibit the chemoreflex. Our results showed no changes in fR, suggesting absence of the tonic chemoreflex activation in response to hypoxia at W1 post-ALI. These data suggest that during the acute stage of moderate (low-dose bleo) and severe (high-dose bleo) ALI, chemoreflex activity trends to be slightly sensitized and blunted, respectively while it becomes significantly sensitized during the recovery stage. Future studies are required to examine the molecular/cellular mechanisms underlying the time-course changes in chemoreflex sensitivity post-ALI.